Pengaruh Konseling Kelompok Dengan Teknik Role Playing Untuk Mengurangi Kecenderungan Perilaku Bullying Di SMP Negeri 02 Singaraja - Desti Br. Pangaribuan; Luh Putu Sri Lestari (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2023)
In this study, the aim was to determine the influence of the application of group counseling services to reduce bullying behavior that occurs in students. The research design used was a quasi-experimental nonequivalent control group design. In this study the population used involved students of class VIII SMP Negeri 2 Singaraja by using a purposive sampling technique. The data analysis method used is in the form of a t-test with the help of the SPSS for Windows version 26 program which is then compared using the effect size, this has the aim of knowing how much influence is generated from the implementation of role playing technique group counseling services to reduce bullying behavior. The data collection instrument used in this study used observation and questionnaires related to bullying behavior. The conclusion in this study is that group counseling with role playing techniques has a strong influence on reducing bullying behavior in students.